Penggunaan Youtube Dalam Pembelajaran Bahasa Arab Intensif di SMP Hikmah Padang Panjang - Muhammad Hanif Basaris (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2021)
This research is empirical research, meaning research that is conducted through a scientific method based on two sets of variables. Using YOUTUBE (x) in teaching Arabic (y) for the intensive class in Islamic boarding school, Padang Panjang. As for the quantitative approach, it is the approach that uses realistic, objective, measured, logical, and organized scientific bases on the existence of numbers and analyzes them using the statistical method. The result of the research is the use of YOUTUBE in intensive Arabic language teaching in the Islamic boarding school of Padang Panjang in the experimental class, with a grade of very good. As for the results of the pre-test in the experimental class, they are with an average value of 64,45. And the results of the test The dimensionality in the experimental class has an average value of 83.7. The t-arithmetic is 2.701 higher than the t-table is 2.110. Then H0 is rejected and Ha is accepted, so the conclusion is that there is an effective YOUTUBE use and raises the result of intensive Arabic language education in Islamic boarding school (Islamic boarding school Padang Panjang).